PENGOLAHAN LIMBAH CAIR ORGANIK SECARA BIOLOGI MENGGUNAKAN REAKTOR ANAEROBIK LEKAT DIAM - Indriyati, Indriyati (Center for Environmental Technology, 2005)
Ã‚Â Ã‚Â Organic waste water can be treated biolocally by using anaerobic fixed bed reactor. Fixed bed reactor is bioreactor which is compleeted with support material inside reactor for bacteria fixation in the surface area of support material. The benefit of using this kind of technology are it needs low energy, low nutrien, low sludge production and could treat high organic concentraion waste water.Ã‚Â Ã‚Â The support materialÃ‚Â has important role in theÃ‚Â Fixed Bed reactor performance, therefore it must be mentioned in several factors those are : size & shape of suport material, ratio of surface area and volume which influences the attach of microorganism, porousity is a waste water volume compare to the total volume and material of support material must inert.Ã‚Â Ã‚Â According to the benefit and the principle of Fixed Bed reactor, this kind of technology can be used to treat the organic high concentration to reduce the organic pollutant.Ã‚Â Kata kunci : anarobic, Fixed Bed.